Strategi Marketing: Efek Event, Viral, dan Affiliate pada Minat Beli Konsumen di Marketplace SHOPEE - Wardhani, Shita Lusi; Manggar Wulan Kusuma (LPPM STIE YKPN Yogyakarta, 2024)
Shopee, Southeast Asia's leading e-commerce platform, has experienced tremendous growth in recent years. This success can be attributed in part to its effective marketing strategy, which has utilized event marketing, viral marketing, and affiliate marketing to drive sales and brand awareness. This research paper provides a comprehensive analysis of Shopee's marketing strategy, examining how the company has successfully used these three channels to engage consumers and achieve its business goals. The data in this study were analyzed using multiple regression analysis with SPSS software. The respondents used in this research were students in Yogyakarta. The analysis results show that event marketing, viral marketing, and affiliate marketing have a positive effect on purchasing interest in the Shopee marketplace. Keywords: Event Marketing, Viral Marketing, Affiliate Marketing, Purchase Interest, Marketplace